PENGARUH PIJAT TEKNIK MARMET DAN AROMATHERAPI LAVENDER TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU POST PARTUM DI KLINIK KARTIKA JAYA - Lidia Lushinta; Erni Wening Sugiastuti (Husada Mahakam, 2022)
The marmet technique is a combination of how to express breast milk and massage the breast so that the milk reflex can be optimal. The use of lavender aromatherapy essential oil can help mothers relax and feel comfortable so that milk production can increase. The method in this study is Quasy Experiment with a non-equivalent control group pretest-posttest design. The population is all primiparous postpartum mothers who gave birth at the Kartika Jaya Samarinda clinic. Sampling technique with Total Sampling as many as 24 people. The results of this study indicate that there is an effect of giving marmet massage and lavender aromatherapy with a value (p-value = 0.000 < = 0.05). There is an effect of giving oxytocin massage with a value (p-value = 0.000 < = 0.05). There was no difference between the intervention group and the control group with a value (p-value = 0.11 > = 0.05) on the increase in breast milk production. There was no difference in the intervention group, namely marmet massage technique and lavender aromatherapy and in the control group, namely oxytocin massage to increase breast milk production in post partum mothers at Kartika Jaya Samarinda clinic.